Manfaat Cek Kesehatan Gratis untuk Deteksi Dini Penyakit - Abu Qosim; Anis Zohriah; Septi Triyana; Mohammad Naufal Al-Rizqi; Ani Pebriani (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The benefits of free health checks in the community are to prevent infectious diseases and further illnesses. Health checks are an effort to detect abnormalities in the body. Health checks should be carried out routinely with the aim of preventing and treating them as quickly as possible. Early detection of disease is a form of education and free health check activities so that the community has awareness to carry out regular health checks as part of promotive and preventive efforts. The main goal of this service is to detect possible diseases and reduce the risk of the disease or treat it more effectively. This service method includes providing health education through the distribution of brochures related to educational materials, accompanied by the implementation of free health checks that involve meetings with Posyandu cadres and the local village head to initiate this service activity. There were 46 participants who took part in the free health check activities. The purpose of this activity was also to help participants better understand the importance of maintaining good health. To help participants better understand the importance of regular health checks to prevent negative impacts in the future, the results of the health checks are used as a guide. On July 30, 2025, the Sukamanah Village community held a free health check socialization program with the aim of increasing public awareness and knowledge about health. The program uses Participatory Action Research (PAR) as a method, benefiting Baros students, the general public, and the community. Outreach efforts have demonstrated that this method has successfully increased public awareness and understanding of health issues. This highlights the need for a more comprehensive health intervention model and research on the program’s long-term impact to maximize positive outcomes for public health.